Women in IT in Sri Lanka: Balancing work and family - Kailasapathy, Pavithra; Adikaram, Arosha S. (Annual Research Symposium, University of Colombo, 2016, 2016)
Despite having made substantial advances in the labour market over the last few decades, women are still underrepresented in science, technology, engineering, and mathematics disciplines universally. Within this context, women’s participation in Information Technology (IT) industry is gaining increased interest, mainly due to the labour shortage and the augmented demand for IT professionals around the globe. The need for increase in women’s participation in the field is found to not only help the demand shortage and thereby the growth of the sector, but also the additional talent and perspective that women would bring into the workforce (Balcita et al., 2002 as cited in Draus et al., 2014). Yet, a common phenomenon for IT companies around the world is the difficulty of attracting and retaining women workers (Cheryan, Plaut, Handron, & Hudson, 2013). Previous studies on women in IT has explored various issues women face in their careers such as discrimination and differential treatment, even when they have good educational degrees (Bhardwaj, 2013), difficulties women face in advancing their careers and hence their underrepresentation in higher managerial positions (Lemons & Parzinger, 2007; Michie & Nelson, 2006), stress they face (Aziz, 2004), emotional cost (Aaltio & Huang, 2007) and the resultant work-family conflicts (Aaltio & Huang, 2007; Bhardwaj, 2013). In this backdrop, we explore the role of work-family in attracting and retaining professional IT women in the IT industry in Sri Lanka. IT is also an important industry for Sri Lanka in terms of earnings, export revenue and employment. It is said to earn US$108 million as total revenue. Further, women in Sri Lanka form approximately 51.6% of the population. Yet, out of the total workforce in the country only 34.7% are women (Department of Census and Statistics, 2015). Of the ICT workforce of 82,824 in Sri Lanka, women’s participation is only 24.8% in 2013, eventhough an increase in the number of women selecting IT-related training is evident (ICTA, 2013).
Keywords: Women; Sri Lanka; IT; Work balance